Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.onc.1207294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemopoietic growth factors on cancer cell lines and their role in chemosensitivity

Abstract: The recombinant growth factors (GFs) erythropoietin (Epo) and granulocyte-macrophage colony stimulating factor (GM-CSF) have important roles in the management of cancer patients. However, the effects of these GFs at a cellular level are not well understood. We examined the effect of GFs alone, and in combination with cytotoxic chemotherapy, in a panel of seven cell lines. Flow cytometric analysis showed varying levels of receptor expression, which correlated with phosphorylated MAPK expression. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 53 publications
(39 reference statements)
3
26
2
3
Order By: Relevance
“…The recent clinical trials and the accumulating data regarding previously unappreciated EPO-mediated functions in cancer cells demonstrate the need to increase our understanding of the role of EPO in tumor progression. However, these findings should not absolutely preclude the use of EPO in cancer patients, since the available data suggest that EPO may affect only certain types of cancer (Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent clinical trials and the accumulating data regarding previously unappreciated EPO-mediated functions in cancer cells demonstrate the need to increase our understanding of the role of EPO in tumor progression. However, these findings should not absolutely preclude the use of EPO in cancer patients, since the available data suggest that EPO may affect only certain types of cancer (Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relatively high doses of EPO (10-250 U/ml) were required to detect proliferation effects. A more recent study found no proliferation effect due to EPO or GM-CSF in leukemic, renal cell carcinoma and colorectal adenocarcinoma cell lines (Liu et al, 2004). The analysis was performed using lower doses of EPO (0-20 U/ml) and it suggested that the proliferative effects of EPO may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26] Indeed, EPOR activation has been observed in the absence of any modification in growth rate. 27 It may be that EPO-EPOR signaling effects on proliferative and anti-apoptotic pathways are dependent on the biochemical context of each cellular model and therefore must be assessed independently.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemotherapy-induced anemia may only seemingly be similar to tumor-induced anemia (33) because different mechanisms may explain insufficient blood formation after drug toxicity compared with systemic inflammation with hormonal and cytokine alterations explaining cachexia. Besides, effects of hematopoietic growth factors on cancer growth, proliferation, and chemosensitivity are still open questions (38). Therefore, it was deemed interesting to evaluate how alterations in self-reported quality of life (HRQL) and performance status relate to objective evaluations of integrative physiology during progressive disease with and without anemia in patients randomized to erythropoietin treatment (39,40).…”
Section: Discussionmentioning
confidence: 99%